1979
DOI: 10.3109/13682827909011346
|View full text |Cite
|
Sign up to set email alerts
|

The Developmental Language Programme. Results from a Five Year Study

Abstract: The setting up and preliminary findings of the Developmental Language Programme have been described in a previous article (1 974). This article presents the findings after five years, from 50 children in the language class setting; and 69 children in the parent programme (language "clinic") under the direction of a speech therapist. In addition to The Wolfson Centre groups, the findings are reported on field trials carried out in local authority class and clinic settings. The large majority of the "programme" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0

Year Published

1982
1982
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 2 publications
0
15
0
Order By: Relevance
“…The importance of screening for language delay lies in the rationale that early identification and intervention may improve the outcome (Cooper, Moodley & Reynell, 1979). Many preschool children with milder language delay improve with age (Herbert & Wedell, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…The importance of screening for language delay lies in the rationale that early identification and intervention may improve the outcome (Cooper, Moodley & Reynell, 1979). Many preschool children with milder language delay improve with age (Herbert & Wedell, 1970).…”
Section: Introductionmentioning
confidence: 99%
“…Parental involvement in therapy has long been recognized as an important means of enhancing a child's development, providing support and assistance to families, and maximizing therapeutic benefits, but as yet there is insufficient research to evaluate this involvement (Cooper et al . , Kaiser and Roberts , Watts Pappas et al . ).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, only 4% of parents reported that they would prefer parent training or an HP to individual therapy. Parental involvement in therapy has long been recognized as an important means of enhancing a child's development, providing support and assistance to families, and maximizing therapeutic benefits, but as yet there is insufficient research to evaluate this involvement (Cooper et al 1979, Watts Pappas et al 2008. Together these findings suggest that workplace factors such as staffing, funding models and the prior clinical experience of SLTs may be influencing service delivery decision-making rather than client preference or external evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Whilst a relatively large number of therapy studies have focused on comparing techniques such as modelling (Leonard 1975, Courtright and Courtright 1976, Ellis Weismer and Murray-Branch 1989, imitation (Connell 1987, Ezell and Goldstein 1989, Connell and Stone 1992 and conversational/sentence recasting (Camarata et al 1994, Nelson et al 1996, Fey et al 1997, Saxton 2005, fewer studies have investigated the effectiveness of different models of therapy provision. Early studies carried out by Cooper et al (1979) investigated the effectiveness of a therapy programme which parents/carers carried out at home, comparing gains in language scores with those of a group for whom the programme was delivered directly by a SLT in a language group. They demonstrated that the home-based intervention delivered by the parents was more effective.…”
Section: Introductionmentioning
confidence: 99%